Choice needs and relationships to happiness by university employees - Yousif Mohammed, Yusra; Ibrahim Aziz, Omar (Zanco Journal of Human Sciences, 2023)
The aim of this study was to examine the relationship between choice needs (Survival, love and Belonging, freedom, power and achievement, Fun) and the relationship with happiness among university employees. Also, know the role of factors such as gender, marital status, income on happiness and choice needs. Plus knowledge of the predictive ability of the choice needs variables for happiness lay in the study sample. The research community consisted of employees of Garmian University, which consisted of employees of all three directorates (University Presidency, Colleges and Research Center) of Garmian University – Kalar township of Sulaimani province. The sample was 47% of the study community, which consisted of 350 employees of both sexes (male and female) equally. Reliance was placed on the (descriptive relationship) approach in this study, and qualitative data were also collected through either the Choice Needs Scale prepared by the researcher, the Oxford Happiness Scale developed by (Hills & Argyle, 2002). with the preparation of demographic information forms. In order to achieve the objectives of the research, statistical analysis (Pearson Correlation Coefficient, Anova, Regression analysis) were used. The results showed that there is a statistically significant relationship between each of the choice needs variables and happiness in the study sample. The effect of marital status on happiness and needs, Survival, Love and Belonging, freedom, power and Achievement) was also observed. Finally, it was found that the need for Fun could be a stronger predictor of happiness in the study sample than other needs.